To adhere or not to adhere: Rates and reasons of medication adherence in hematological cancer patients. (January 2016) - Hall, Alix E.; Paul, Chris; Bryant, Jamie; Lynagh, Marita C.; Rowlings, Philip; Enjeti, Anoop; Small, Hannah
Abstract: To conduct a comprehensive review to examine among hematological cancer patients: (1) rates of adherence to self-administered cancer treatments; and (2) factors impacting on their adherence. Fifty two eligible publications were identified. The majority focused on Chronic Myeloid Leukaemia (CML) ( n  = 40) and Acute Lymphoid Leukaemia (ALL) ( n  = 11) patients. Adherence rates varied and depended on the definition and measures used. Patient understanding about their disease and treatment, and forgetting to take their medication impacted on patients' level of adherence; while the use of reminders reduced forgetfulness. There is a lack of valid and reliable information relating to medication adherence of hematological cancer patients. Based on the limited data available we provide a profile of CML and ALL patients at potential risk of medication non-adherence, as well as a proposed checklist that can be used by health care providers in assessing and supporting patients in adhering to their medication.